Characterization and differentiation of boiled pork from Tibetan, Sanmenxia and Duroc × (Landrac × Yorkshire) pigs by volatiles profiling and chemometrics analysis. (April 2020) - Han, Dong; Zhang, Chun-Hui; Fauconnier, Marie-Laure; Mi, Si
Graphical abstract: Highlights: A total of 61 volatile compounds were identified and quantified. 25 volatile compounds were considered as odour-active compounds. Boiled pork was clearly separated into three groups by chemometric analysis. The potential flavour markers were found in boiled pork of different breeds of pigs. GC–MS/O coupled with E-nose method is feasible to distinguish the different boiled pork. Abstract: To characterize and differentiate boiled pork from three different pig breeds (Tibetan, Sanmenxia and Duroc × (Landrace × Yorkshire)), the volatile compounds in each were analysed by gas chromatography-olfactometry-mass spectrometry (GC–MS/O) and electronic nose (E-nose) combined with chemometrics analysis. In total, 61 volatile compounds were identified, among which 25 compounds were selected as odour-active compounds in boiled pork. Moreover, seven odour-active compounds (hexanal, nonanal, 1-octen-3-ol, dimethyl disulphide, heptanal, 2-pentylfuran and 2-ethylfuran) were the main contributors to the integral flavour of boiled pork due to their higher odour activity values (OAVs) ranging from 17.3 to 524.2. The odour-active compounds were examined by principal component analysis (PCA), agglomerative hierarchical clustering (AHC) and partial least squares-discriminant analysis (PLS-DA). The results showed that boiled pork from the three pig breeds could be clearly distinguished, and twelve odour-active compounds, including ( E, E )-2, 4-decadienal, ethyl hexanoate, dimethyl disulphide, hexanal, 2-acetylthiazole, ( E )-2-nonenal, 1-octen-3-ol, ( E, E )-2, 4-nonadienal, heptanal, ( E )-2-octen-1-ol, styrene and ( E )-2-octenal, were determined as potential flavour markers for discrimination. This study indicated that GC–MS/O and E-nose with chemometrics analysis are feasible methods to characterize and discriminate boiled pork from three pig breeds.